Microorganisms in foods 8 use of data for assessing process control and product acceptance - International Commission on Microbiological Specifications for Foods; #aSpringerLink (Online service). (New York Springer, 2011)
aContinuing the ICMSF series, Microorganisms in Foods 8provides practical guidance on appropriate testing of food processing environments, processing lines, shelf life and finished product to enhance the safety and microbiological quality of the food supply. Part I, Principles of Using Data in Microbial Control, summarizes the principles of Microorganisms in Foods 7: Microbiological Testing in Food Safety Management (2002), which illustrates how HACCP and Good Hygienic Practices (GHP) provide greater assurance of safety than microbiological testing, and also identifies circumstances where microbiological testing may play a useful role. Part II, Applications of Principles to Product Categories, updates and expands Part II of Microorganisms in Foods 2: Sampling for Microbiological Analysis: Principles and Specific Applications (1986) and builds on Microorganisms in Foods 6: Microbial Ecology of Food Commodities (2nd edition, 2005) with recommended tests and specific criteria for 19 food product categories to evaluate the effectiveness of controls. Microorganisms in Foods 8 is intended for anyone using microbiological testing or engaged in setting microbiological criteria including government, food processors and the customers they supply. This book provides actionable information for food quality assurance professionals, food microbiologists, food technologist, veterinarians, public health workers and regulatory officials. This peer reviewed book was prepared by the International Commission on Microbiological Specifications for Foods (ICMSF), with assistance from a limited number of consultants. The ICMSF was formed in response to the need for internationally acceptable and authoritative guidance on microbiological limits for foods in international commerce. Currently the membership consists of 17 food microbiologists and public health professionals from eleven countries, drawn from government, universities, and food processing and related industries. Also available Microorganisms in Foods 7: Microbiological Testing in Food Safety Management, 2002 (978-0-306-47262-6) Microorganisms in Foods 6: Microbial Ecology of Food Commodities, 2nd edition 2005 (978-1-4419-3465-9) Microorganisms in Foods 5: Characteristics of Microbial Pathogens, 1996 (978-0-412-47350-0)
Preface -- Contributors and Reviewers -- Abbreviations Used in the Book -- Part I. Principles of Using Data in Microbial Control -- 1. Utility of Microbial Testing for Safety and Quality -- 2. Validation of Control Measures -- 3. Verification of Process Control -- 4. Verification of Environmental Control -- 5. Corrective Actions to Re-Establish Control -- 6. Microbiological Testing in Customer-Supplier Relations -- Part II. Applications of Principles to Product Categories -- 7. Applications and Use of Criteria and Other Tests -- 8. Meat Products -- 9 Poultry Products -- 10. Fish and Seafood Products -- 11. Feeds and Pet Food -- 12. Vegetables and Vegetable Products -- 13. Fruits and Fruit Products -- 14. Spice, Dry Soups and Asian Flavorings -- Cereals and Cereal Products -- 16. Nuts, Oilseeds, Dried Legumes and Coffee -- 17. Cocoa, Chocolate and Confectionary -- 18. Oil- and Fat-based Foods -- 19. Sugar, Syrups and Honey -- 20. Non-Alcoholic Beverages -- 21. Water -- 22. Eggs and Egg Products -- 23. Milk and Dairy Products -- 24. Shelf-Table Heat Treated Foods -- 25. Dry Foods for Infants and Young Children -- 26. Combination Foods -- Appendix 1. Sampling Considerations and Statistical Aspects of Sampling Plans -- Appendix 2. Calculations for Chapter 2 -- Appendix 3. ISO Methods Referenced in Tables -- Appendix 4. Objectives and Accomplishments of the ICMSF -- Appendix 5. ICMSF Participants -- Appendix 6. ICMSF Publications -- Appendix 7. Sponsors of ICMSF Activities.
College of Science Library has electronic copy. Kindly send us a message through cslib@science.upd.edu.ph using your UP mail for the copy of this material.
Electronic reproduction.
Keywords: Food -- Microbiology; Electronic books